Factors Analysis And Profit Achievement For Trading Company By Using Rough Set Method - Sembiring, Muhammad Ardiansyah; Azhar, Zulfi (International Journal of Artificial Intelligence Research, 2017)
This research has been done to analysis the financial raport fortrading company and it is  intimately  related  to  some  factors  which  determine  the profit of company. The result of this reseach is showed about  New Knowledge and perform of the rule. In  discussion, by followed data mining process and using Rough Set method. Rough Set is to analyzed the performance of the result. This  reseach will be assist to the manager of company with draw the intactandobjective. Rough set method is also to difined  the rule of discovery process and started the formation about Decision System, Equivalence Class, Discernibility Matrix,  Discernibility Matrix Modulo D, Reduction and General Rules. Rough set method is efective model about the performing analysis in the company. Keywords : Data Mining, General Rules, Profit,. Rough Set.